1980
DOI: 10.1038/clpt.1980.198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminum hydroxide on fluoride metabolism

Abstract: Aluminum inhibits intestinal absorption of fluoride in animals but little information is available about man. To determine whether and to what extent aluminum affects fluoride absorption in man, effects of aluminum hydroxide on fluoride metabolism were studied under controlled dietary conditions. Relatively small amounts of aluminum hydroxide were used (30 ml three times daily, containing a total of 1.8 gm aluminum, were given for several weeks). Fluoride balances were determined in control studies and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Numerous studies showed that aluminium could inhibit fluoride absorption (Spencer et al, 1980;Allain et al, 1996). A study conducted by Spencer and Kramer showed that intake of small doses of Al(OH) 3 increased urinary fluoride excretion and reduced fluoride absorption in the blood (Spencer & Kramer, 1985).…”
Section: Influence Of Al 3+ On Accumulation and Permeability Of Fluoridementioning
confidence: 99%
“…Numerous studies showed that aluminium could inhibit fluoride absorption (Spencer et al, 1980;Allain et al, 1996). A study conducted by Spencer and Kramer showed that intake of small doses of Al(OH) 3 increased urinary fluoride excretion and reduced fluoride absorption in the blood (Spencer & Kramer, 1985).…”
Section: Influence Of Al 3+ On Accumulation and Permeability Of Fluoridementioning
confidence: 99%
“…Existen estudios in vivo que evidencian que la biodisponibilidad de fluoruro está altamente influenciada por la composición de los alimentos ingeridos. Así, la biodisponibilidad de NaF en humanos disminuye si existe una administración simultánea de leche (Trautner y Einwag, 1989) Spencer, 1980b;Cerklewski, 1987;Tsuchida y col., 1992). Todo lo anterior indica que en los estudios in vitro donde se evalúa la bioaccesibilidad y la biodisponibilidad de fluoruro es necesario ensayar no sólo el alimento que contiene el fluoruro, si no cualquier alimento, tanto sólido como líquido, ingerido simultáneamente.…”
Section: Discussionunclassified